Sustained increase in platelet aggregation after the cessation of clopidogrel. (February 2016) - Djukanovic, Nina; Todorovic, Zoran; Zamaklar‐Trifunovic, Danijela; Protic, Dragana; Dzudovic, Boris; Ostojic, Miodrag; Obradovic, Slobodan
Summary: This study shows that the abrupt cessation of one‐year clopidogrel treatment was not associated with thrombotic events in a prospective, multicentre study that enrolled 200 patients subjected to coronary stent implantation and treated with aspirin + clopidogrel 1 year after the stent placement. The aim of the study was to investigate the causes of a sustained increase of platelet aggregability, considering that the values of platelet aggregation stimulated with ADP + PGE1 (ADPHS values) significantly increased 10–90 days after the cessation of clopidogrel. Values of platelet aggregation induced by thrombin receptor activating peptide (TRAP values) and arachidonic acid (ASPI values) were divided into quartiles on the basis of ADPHS values 10 days after stopping clopidogrel (ADPHS10 ). There was a significant difference between TRAP values divided into quartiles according to ADPHS10, 10, 45 and 90 days after stopping clopidogrel ( P  <   0.001, all), and ASPI values across the same quartiles 10 and 45 days after the cessation of clopidogrel ( P  =   0.028 and 0.003). The results of the study indicate that patients with early pronounced rebound phenomena to clopidogrel termination have a long‐term (at least 90 days) increased platelet aggregation to other agonists such as thrombin‐related activated protein and arachidonic acid, suggesting the complex mutual relationship of various factors/agonists influencing the function of platelets.